Analisis Aplikasi Teori Myra Levine Pada Dyspareunia Wanita Setelah Histerektomi - Barkah Wulandari (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2018)
Background : Hysterectomy is one of the surgical actions that causes anatomical changes. Such changes create problems in terms of lumbrication and dyspareunia. The state of dyspareunia causes a woman to feel an uncomfortable condition during sexual intercourse and the woman is prepared to adapt to the condition. This study is intended to provide an overview of the myra Levine theory of dyspareunia in women after hysterectomy. Method : This research uses qualitative approach with phenomenology strategy with sampling technique using purposive sample. In-depth interviews were conducted on 4 respondents who had a history of post hysterectomy on benign and sexual active. Respondents previously performed dyspareunia assessment with FSFI (Female Sexual Function Index) questionnaire. Result : Were women after hysterectomy took time off as energy conservation. Early adaptation after hysterectomy, Respondents said feeling dyspareunia on sexual activity returned after hysterectomy, subsequently the respondents chose actions taken to reduce dyspareunia and positive self-image on an occurrence of dyspepsia can help adaptation in structural conservation. Conclusion : The third point in this study is required nurse role in providing discharge planning: Health promotion as the fulfillment of personal and social conservation.